2017
DOI: 10.2741/s468
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal aberrations clastogens vs aneugens

Abstract: Current anticancer therapy may be one of the most important exogenous sources of exposure to genotoxic agents in US, Japan, and Europe, where approximately 40-55 percent of the population is diagnosed with cancer at a certain point in their life. This review focuses on recent efforts to integrate a novel biomarker, gamma-H2AX, into anticancer drug screening to classify the mode of action (MoA) for genotoxic outcome into clastogenicity and aneugenicity, a distinction that has considerable impact on risk assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 115 publications
(136 reference statements)
0
12
0
Order By: Relevance
“…The so‐called linear‐no‐threshold model was generally applied to genotoxicological risk assessment. Numerous studies have shown nonlinear genotoxic mechanisms predominantly associated with aneuploidy‐inducing agents (Bolt et al, ; Crump, ; Elhajouji et al, ; ICH, ; Bevan and Harrison, ; Mishima, ), but also with clastogens acting as indirect inducers of DNA double‐strand breaks (Lynch et al, ; Bryce et al, ; Johnson et al, ). Although the primary goal of this work was not the demonstration of nonlinear dose–response metrics, the concentrations used for ETO allowed us to identify a no‐observed genotoxic effect level at 0.5 μmol/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The so‐called linear‐no‐threshold model was generally applied to genotoxicological risk assessment. Numerous studies have shown nonlinear genotoxic mechanisms predominantly associated with aneuploidy‐inducing agents (Bolt et al, ; Crump, ; Elhajouji et al, ; ICH, ; Bevan and Harrison, ; Mishima, ), but also with clastogens acting as indirect inducers of DNA double‐strand breaks (Lynch et al, ; Bryce et al, ; Johnson et al, ). Although the primary goal of this work was not the demonstration of nonlinear dose–response metrics, the concentrations used for ETO allowed us to identify a no‐observed genotoxic effect level at 0.5 μmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…In general, genotoxic compounds like clastogens and aneugens can induce micronuclei (MN). MN are small, extra‐nuclear chromatin bodies surrounded by a nuclear envelope, which are not incorporated into the nucleus of a daughter cell after nuclear division (Fenech and Morley, ; Fenech, ; Vanhauwaert et al, ; Mishima, ). MN are indicative of chromosome or genome mutations and are commonly observed in cancer development (Kirsch‐Volders et al, ; Bolognesi et al, ; Morita et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A MN is induced by direct DNA damage (clastogenicity) or by retardation of chromosome segregation (aneugenicity). Revealing the clastogenic or aneugenic mode of action (MoA) is important, especially in pharmaceutical development, which needs to define a threshold of genotoxicity [2]. In general, there is no genotoxicity threshold for clastogens, because direct interaction between a chemical and DNA cannot be ruled out even at very low exposure levels.…”
Section: Introductionmentioning
confidence: 99%
“…by ionizing radiation) but also by DNA single-strand breaks (SSB) after treatment with UV irradiation, topoisomerase inhibitors, and reactive oxygen species [6, 7]. The combination of MN test and γH2AX detection on a high-throughput platform will make it possible to discriminate aneugens from clastogens in the early screening stages because it was reported that aneugens do not form γH2AH foci [2] whereas clastogens do. Furthermore, imaging analysis makes it possible to morphologically discriminate γH2AX foci from pan-nucleic γH2AX staining, which is believed to be induced by non-genotoxic events, such as apoptosis [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, γH2AX is also used as a marker of genotoxicity in pharmaceutical drug development [ 9 ]. Because the early stage of drug development requires high-throughput screening (HTS) assays that can rapidly evaluate a variety of chemical candidates, the simple methodology of the γH2AX assay makes it well-matched to this purpose.…”
Section: Introductionmentioning
confidence: 99%